Social service in medicine in Mexico. An urgent and possible reform. - Gustavo Nigenda (Instituto Nacional de Salud Pública, 2013)
One third of the primary care units in the public system keeps being covered exclusively by interns. It is shown that with the resources available in the System for Social Protection in Health it is possible to hire graduate health personnel for all Ministry of Health rural units. It is necessary to modify the current legislation to impede an intern to be located in units without supervision of a graduate doctor. There is an urgent need for a reform of social service in medicine that responds both to the institutional modernization and to the increased capacity of the newly insured to demand high-quality services.